Impacts of Converting Native Grassland into Arable Land and an Avocado Orchard on Soil Hydraulic Properties at an Experimental Farm in South Africa - Jestinos Mzezewa (Agronomy)
The main objective of this study was to evaluate the changes in soil water retention curve (WRC) and pore size distribution in the 0–10, 10–20, and 20–30 cm layers following grassland conversion into arable land and an avocado orchard. Undisturbed soil cores were sampled using cylindrical metal cores to determine WRCs. The RETC program was used to fit the van Genuchten equation to the measured water retention data. The maximum equivalent radius (r) of soil pores retaining water at various matric potentials was calculated using the capillary rise equation. Significant differences between treatments were observed mainly in the 10–20 cm layers. Greater θs, n, and α in grassland were attributed to low bulk density and high soil organic carbon. Soil compaction in arable land and an avocado orchard was attributed to soil disturbance. The grassland had a greater share of macro- and mesopore volumes and large air capacity than the arable and avocado orchard. Overall, the results indicated that the conversion of native grassland causes substantial changes in soil hydraulic properties that could impact crop growth and the environment.